EXERCISES AS A MEANS OF RESTORING A PERSON'S VITALITY" (Scientific journal of the Fergana State University, 2024)
Theoretical knowledge about the “vital energy” inherited from our ancestors for our organs and structures, theoretical knowledge about its conservation and restoration through physical exercise.